BENCHMARK FOR NUMERICAL ANALYSIS OF STEEL AND COMPOSITE FLOORS EXPOSED TO FIRE USING A GENERAL PURPOSE FEM CODE - Both, Ioan; Wald, František; Zaharia, Raul (Journal of Applied Engineering Science, 2016)
Increasing number of tests on structures in fire conditions offers valuable information regarding the global and local behaviour. The output data of these experiments can be considered to be a good opportunity for validation of numerical models. Nevertheless, in some fortuitous cases, inaccurate input of numerical models may lead to results matching the experimental ones. The validation and/or verification of advanced calculation models for the fire design are an important issue not only for computer code developers, but also for designers and authorities. The validation of an advanced calculation model is usually linked with the comparison to experimental results, while the verification is related to the comparison to analytical solutions or to the results given by other computer codes. The paper presents a benchmark for both thermal and structural analysis of a composite floor subjected to fire using beam and shell elements. The numerical analysis is performed with a general purpose finite-element code. The input and the output of the thermo-mechanical analysis are detailed, with respect to a real scale fire test.